Copper Sources for Sod1 Activation - Stefanie D. Boyd; Morgan S. Ullrich; Amelie Skopp; Duane D. Winkler (MDPI AG, 2020)
Copper ions (i.e., copper) are a critical part of several cellular processes, but tight regulation of copper levels and trafficking are required to keep the cell protected from this highly reactive transition metal. Cu, Zn superoxide dismutase (Sod1) protects the cell from the accumulation of radical oxygen species by way of the redox cycling activity of copper in its catalytic center. Multiple posttranslational modification events, including copper incorporation, are reliant on the copper chaperone for Sod1 (Ccs). The high-affinity copper uptake protein (Ctr1) is the main entry point of copper into eukaryotic cells and can directly supply copper to Ccs along with other known intracellular chaperones and trafficking molecules. This review explores the routes of copper delivery that are utilized to activate Sod1 and the usefulness and necessity of each.